Strategi Peningkatan Kinerja Keagenan Kapal dalam Rangka Menunjang Kelancaran Clearance in dan Clearance Out di PT Temas Shipping Cabang Surabaya - Kevin Alif Fikriansyah; Romanda Annas; Eka Nurmala Sari (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The shipping industry continues to grow, requiring companies to compete by providing excellent services. Ship agencies play a crucial role in operations, particularly in clearance in and clearance out processes. PT. Temas Shipping faces challenges such as expired documents, inaccurate vessel information, and limited facilities, making it necessary to implement strategies to enhance ship agency performance in clearance in and clearance out processes.The objective of this study is to identify the obstacles encountered in the clearance in and clearance out processes at PT. Temas Shipping Surabaya Branch, assess the impacts of these challenges, and explore strategies to improve ship agency performance in facilitating clearance in and clearance out processes. This research employs a qualitative approach. Data is collected through observations, interviews with relevant sources, and document analysis related to clearance in and clearance out processes at PT. Temas Shipping Surabaya Branch. The data collection techniques include observation, interviews, and documentation, while data analysis follows a descriptive approach. The research findings highlight several obstacles in the clearance in and clearance out processes, primarily the limited human resources, which result in delays in document processing and disrupt clearance procedures for vessels under PT. Temas Shipping Surabaya Branch. The discussion also covers the impacts of clearance in and clearance out processes, including effects on PT. Temas Shipping Surabaya Branch’s internal productivity, customer trust and satisfaction, financial aspects, and supply chain efficiency. Lastly, the study explores strategies to improve performance, such as enhancing document management systems, developing human resources into professionals, providing rewards for agents, and conducting regular evaluations and monitoring.